Robotic Journalism and Nursing. Issue 5 (September 2015) - McCartney, Patricia
Abstract : Robotic journalism is the use of software algorithms designed to generate written articles. Summarized structured quantifiable data are key content in healthcare communications. New journalism technology may soon challenge nurse authors and editors to incorporate robot generated content. Will we be reading nursing literature generated by robots in the near future?